2016
DOI: 10.1152/ajplung.00461.2015
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor, a role in COPD

Abstract: Macrophage migration inhibitor factor (MIF) is a pluripotent cytokine associated with several different inflammatory conditions, but its role within lung inflammation and chronic obstructive pulmonary disease (COPD) is unclear. This study aimed to examine MIF in both stable COPD and during acute exacerbations (AECOPD). The study included 433 patients with COPD aged 41–76 and 325 individuals from the Bergen COPD cohort study who served as controls. All patients had an FEV1 of <80% predicted, FEV1/FVC ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
19
1
Order By: Relevance
“…Lastly, CXCR4 is a chemokine receptor for pro-inflammatory mediators such as macrophage migration inhibitor factor (MIF), which is a pleiotropic cytokine that antagonizes both apoptosis and premature senescence [ 56 , 57 , 58 ]. It has been shown to be elevated and implicated in the pathogenesis of COPD [ 59 ]. Together, upregulation of these genes suggest that these non-polarized macrophages were also pro-inflammatory in nature and suppress inflammation resolution and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, CXCR4 is a chemokine receptor for pro-inflammatory mediators such as macrophage migration inhibitor factor (MIF), which is a pleiotropic cytokine that antagonizes both apoptosis and premature senescence [ 56 , 57 , 58 ]. It has been shown to be elevated and implicated in the pathogenesis of COPD [ 59 ]. Together, upregulation of these genes suggest that these non-polarized macrophages were also pro-inflammatory in nature and suppress inflammation resolution and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…A third study suggested that peripheral blood mononuclear gene expression of MIF inversely correlated with disease severity as measured by percent emphysema and spirometric evidence of airway obstruction (9). Finally, a recent study, and the largest of its kind, has shown that, although MIF was increased in moderate disease (GOLD II) compared with healthy never, current, and former smokers, there was a significant decrease in circulating MIF among patients with severe and very severe disease (GOLD III, IV) (61). Overall these studies suggest that although MIF may be increased among healthy smokers or smokers with moderate disease, circulating levels of MIF fall as the disease progresses.…”
Section: Mif In Animal Models and Human Studies Of Age-related Lung Dmentioning
confidence: 98%
“…[52]. Additionally, impairment of autophagy is also associated with an increase in ROS-dependent macrophage migration inhibitory factor (MIF) activity [57], which further promotes pro-inflammatory cytokine (such as IL-1β) production and release [54], as well as hyper-inflammatory response in COPD airways [58]. In addition, as a proof of concept, macrophages isolated from COPD subjects are defective in autophagy-mediated phagocytosis (xenophagy) resulting in impaired clearance of bacteria/viruses [5961].…”
Section: Introductionmentioning
confidence: 99%